DERAJAT DEASETILASI KITOSAN DARI CANGKANG KERANG DARAH DENGAN PENAMBAHAN NaOH SECARA BERTAHAP - Syaiful Bahri; Erwin Abd. Rahim; Syarifuddin Syarifuddin (KOVALEN: Jurnal Riset Kimia, 2015)
The study about raising of chitosan deacetilation degree in Anadara granosa by gradually adding NaOH has been done. The aim of the research was to study the influence of gradually added NaOH on the raising of chitosan deacetilation. The degree of chitosan deacetilation was determined by using spectroscopy of Fourier Transform Infra Red (FTIR). The result showed that the deacetilation degree increase with the increase of NaOH added i.e 79%; 85,9%; 89,95% for the first, the second and the third addition of NaOH with 3, 6 and 9 hours of the reaction the respectively. Keywords: Anadaragranosa; Chitin; Deacetilation Degree; Chitosan